Systematic Bibliometric Analysis: Digital Human Resource Management Studies for Future Research - 'Alam, Ghasa Faraasyatul (Klabat Journal of Management, 2025)
Digital progress in the current era, marked by rapid and widespread technological advancements, has become a key factor in determining individual success, societal development, and effective human resource management. Various developments in digital technology, including digital literacy, have made knowledge in the field of digital human resource management increasingly complex for future research. The aim of this study is to conduct a bibliometric analysis of digital human resource management research in the context of digital transformation by thoroughly reviewing existing literature. The study utilizes Publish or Perish (PoP) and VOSviewer software to generate readable bibliometric network visualizations. Through the initial screening and selection process, several studies met the inclusion criteria, with references drawn specifically from literature sources included in the final analysis. The findings reveal that the body of literature on digital human resource management for future research is composed of several thematic clusters. Each cluster reflects a recurring set of keywords that outline current research trends and provide a meaningful snapshot of real-world developments in the field. In conclusion, this research enhances understanding and digital literacy related to the evolution of digital human resource management studies and highlights its potential within the broader scope of digital transformation in the modern world.